Morquio B disease: a case report - Tara Gholamian; Harpreet Chhina; Sylvia Stockler; Sylvia Stockler; Anthony Cooper; Anthony Cooper (Frontiers Media S.A., 2024)
Mucopolysaccharidosis IV type B, or Morquio B disease (MBD), is an autosomal recessive disorder caused by a genetic mutation in GLB1 gene encoding for β-galactosidase on chromosome 3p22.33. β-galactosidase deficiency can result in two different conditions, GM1 gangliosidosis and MBD, of which MBD has a milder phenotype and presents later in life with keratan sulfate accumulation in the retina and cartilage. In this case report, we present a patient diagnosed with MBD at the age of 5 after initially presenting with Morquio dysostosis multiplex and characteristic radiographic findings. Genetic testing confirmed that the patient has β-galactosidase deficiency due to mutation W273l/N484K on GLB1 gene. The patient exhibited elevated mucopolysaccharide levels in urine at 18 mg/mmol and demonstrated an abnormal band pattern of urine oligosaccharides on electrophoresis. The activity of β-galactosidase in his white blood cells was reduced to 12.3 nmol/h/mg protein. At the time of diagnosis, the patient did not present with gait and ambulation issues, but his ability to walk progressively deteriorated in his adolescence as a result of instability and pain in the ankle, knee, and hip joints, accompanied by a global decrease in muscle strength. This case report is the first in the literature to provide an in-depth exploration of the orthopedic treatment and follow-up received by a young adolescent with MBD to provide symptom relief and improve walking ability.